Penerapan Model Pembelajaran Kooperatif Tipe STAD Untuk Meningkatkan Keaktifan Dan Hasil Belajar IPS Pada Siswa Kelas VB SDN 1 Kaliwuluh Semester I Tahun Pelajaran 2020/2021 - Prabawati, Yunita A. (Social, Humanities, and Educational Studies (SHES): Conference Series, 2020)
This study aims to increase activity and low social studies learning outcomes. The implementation of this Classroom Action Research was carried out in two cycles, with each cycle consisting of planning, implementing actions, observing, and reflecting. The subjects of this study were students of class VB SDN 01 Kaliwuluh which opened 21 students with the object of research on student activities and learning outcomes. From the results of data analysis it is known that in each cycle there is an increase in student activity and learning outcomes. In the condition, the percentage of student learning activities is only 22.66%, while the learning outcomes are 63.64% below the KKM. In the first cycle, learning activities increased to 62.99% and learning outcomes reached 68.18%. In the second cycle, student activity increased to 77.89% and learning outcomes reached 86.36%. Based on Classroom Action Research, it can be said that the application of the STAD type cooperative learning model can increase the activeness and learning outcomes of social studies students in class V B SDN 01 Kaliwuluh in semester 1 of the 2020/2021 academic year.